2021
DOI: 10.3390/e23060763
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Classification Models and Relevant Features on Nonalcoholic Steatohepatitis Using Random Forest

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome and is the most common cause of chronic liver disease in developed countries. Certain conditions, including mild inflammation biomarkers, dyslipidemia, and insulin resistance, can trigger a progression to nonalcoholic steatohepatitis (NASH), a condition characterized by inflammation and liver cell damage. We demonstrate the usefulness of machine learning with a case study to analyze the most important features in random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…We consider RF an excellent, reliable, stable, and robust nonlinear classifier compared to conventional approaches. RF can address nonlinearity, as has been demonstrated previously [34,53]. In our study, RF not only performed fairly well but also selected some interesting features as most relevant to Listeria-related mortality.…”
Section: Statistics and Machine Learningsupporting
confidence: 76%
See 1 more Smart Citation
“…We consider RF an excellent, reliable, stable, and robust nonlinear classifier compared to conventional approaches. RF can address nonlinearity, as has been demonstrated previously [34,53]. In our study, RF not only performed fairly well but also selected some interesting features as most relevant to Listeria-related mortality.…”
Section: Statistics and Machine Learningsupporting
confidence: 76%
“…We used the RF implementation in the R package randomForest [31]. Several biomedical publications, such as ones on steatohepatitis, have shown that RF is an excellent, reliable, stable, and robust nonlinear classifier compared to other machine-learning classifiers [32][33][34]. RF works by building many decision trees in which features predict a categorical outcome (e.g., mortality).…”
Section: Feature Selection Using Rfmentioning
confidence: 99%
“…Serum ferritin and insulin were selected with high sensitivity and specificity using the LASSO approach with a sensitivity of 70%, specificity of 79%, and area under the curve of 0.79 [16]. Another study by Garcia-Carretero et al used random forest (RF) models for predicting patients at risk of developing NASH in 1525 patients [15]. The electronic health records were used to assess the presence of NASH.…”
Section: Ai In Predicting Risk Factors Of Nafldmentioning
confidence: 99%
“…Four features that were the most relevant included insulin resistance, ferritin, serum levels of insulin, and triglycerides. Random forest-based modeling demonstrated that machine learning could be used to improve interpretability, produce an understanding of the modeled behavior, and demonstrate how far certain features can contribute to predictions [15].…”
Section: Ai In Predicting Risk Factors Of Nafldmentioning
confidence: 99%
“…Insulin resistance (IR) is defined as an impaired biological response to insulin stimulation of target tissues mainly including the liver, muscle, and adipose tissue. Insulin resistance syndrome, also known as metabolic syndrome, is associated with a broad spectrum of diseases such as obesity, hyperglycemia, hypertension, dyslipidemia, non-alcoholic fatty liver disease, cardiovascular disease, polycystic ovarian syndrome, and type 2 diabetes mellitus (Allahbadia and Merchant, 2008;Willard et al, 2016;Cortés-Rojo et al, 2020;García-Carretero et al, 2021). Insulin resistance is mainly related to excess body fat and also genetic causes, which affects as many as one in three Americans and becomes a tremendous burden for the healthcare system of the United States (Balasubramanyam, 2006;McCarthy, 2014;Sharma et al, 2019;Rajesh and Sarkar, 2021).…”
Section: Introductionmentioning
confidence: 99%